Coating graphene paper with 2D-assembly of electrocatalytic nanoparticles : a modular approach toward high-performance flexible electrodes - Xiao, Fei (2013)
The development of flexible electrodes is of considerable current interest because of the increasing demand for modern electronics, portable medical products, and compact energy devices. We report a modular approach to fabricating high-performance flexible electrodes by structurally integrating 2D-assemblies of nanoparticles with freestanding graphene paper. We have shown that the 2D array of gold nanoparticles at oil–water interfaces can be transferred on freestanding graphene oxide paper, leading to a monolayer of densely packed gold nanoparticles of uniform sizes loaded on graphene oxide paper. One major finding is that the postassembly electrochemical reduction of graphene oxide paper restores the ordered structure and electron-transport properties of graphene, and gives rise to robust and biocompatible freestanding electrodes with outstanding electrocatalytic activities, which have been manifested by the sensitive and selective detection of two model analytes: glucose and hydrogen peroxide (H2O2) secreted by live cells. The modular nature of this approach coupled with recent progress in nanocrystal synthesis and surface engineering opens new possibilities to systematically study the dependence of catalytic performance on the structural parameters and chemical compositions of the nanocrystals.